ARCHITECTURAL DESIGN PRINCIPLES FOR AUTISTIC CHILDREN'S EDUCATION AND REHABILITATION CENTERS - Irtenk, Tugce; Akbulut, M. Tolga (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2015)
In the scope of this paper, the principles of planning of the special education and rehabilitation centers for autistic children's education will be examined according to the effects of designed environment on the individuals. This paper is prepared according to the study named Autistic Children's Architectural Investigation of Special Education And Rehabilitation Centers completed in the master Program of Architectural Design in Yildiz Technical University in 2011. The studies in Turkey and the world have proved that the prevalence of coincides with autism has increased. Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) which is known and used in the world as scientific criteria of evaluation and measurement of development shows us one in every 150 children effected by the autism. Autism can be seen in every socio-economic level, and is not specifically associated with any class, country or culture. Autism is a lifelong disorder and as far as it is known, education is the only treatment. School enrollment rate for autistic children is inadequate both in the public and private schools in Turkey. Early diagnosis and an early start in early education about autism are very important. It is proved by many scientists that the children starting education 30-40 hours in a week in early ages have made great strides in social integration. Ensuring the integration of autistic children with the community can only be realized by education and the specially designed physical infrastructures of education and rehabilitation centers. This paper aims to give a brief definition of autism, characteristics of children with autism and will focus on autism education approaches, discuss the planning principles of existing education and rehabilitation centers in Turkey and in the world and finally will attempt to put forward architectural suggestions for the new centers designs. Architectural suggestions will include general design principles, required spaces (education spaces, sport facilities, common areas, administrative offices, service spaces) and the relations within these spaces in these centers.
Keywords: Architecture; Design; Autistic; Rehabilitation Center; Education; Education & Educational Research